INFORMED CONSENT DAN OTONOMI MANUSIA - J. Sudarminta (Studia Philosophica et Theologica, 2001)
One of the crucial points in territory of medical service is ethical problem of informed consent. Is it necessary that a patient should be involved in decision making with regard to her/his medical treatment in spite of her/his ignorance? The question is crucial, as in fact a patient comes to a medicaldoctor or hospital simply because of his/her surrender to be treated insofar as he/she can recover his/ her health. It is almost impossible to consider that by coming to a hospital the patient is doubt about medical treatment done in that hospital. In this article I try to draw some ethical considerations up from the fact that in spite of the patient’s ignorance regarding medical treatment, he is the autonomous person. The logical consequence of autonomy is that the person is free from any assumption that can reduce his/her authority upon his/her body. So, the article shall delve into discovering the relationship between informed consent and human autonomy.